Intergroup Encounters Among Wild White-Faced Capuchins (Cebus imitator) at a Densely Populated Field Site: Insights into Frequency, Intensity, and Participation - Sarah A. Kovalaskas; Agostina Colosimo; Vasco Alexandre Martins; Juan Carlos Ordoñez; Elena Morera Saborío; Jacinta C. Beehner; Thore J. Bergman; Marcela E. Benítez (International Journal of Primatology, 2026)
Intergroup encounters (IGEs) are a major feature of social life for group-living primates, influencing access to resources, reproductive opportunities, and territory. We examined IGE frequency, intensity, and participation in a high-density population of wild white-faced capuchin monkeys ( Cebus imitator ) at the Capuchinos de Taboga research project in Guanacaste, Costa Rica, using 4 years of data on three capuchin groups (4,984 observation hours, 218 IGEs). The IGE rates at Taboga (0.044/hr) were two to four times higher than those at nearby lower-density sites and did not vary with rainfall or temperature. More than half of IGEs involved high-intensity aggression (chases or contact aggression). Ordinal logistic models showed that the number of focal group participants was a consistent predictor of escalation, with each additional participant increasing the odds of higher intensity by 1.4 times, while ecological variables had little explanatory value. Participation was more likely for older individuals, males, alphas, and when individuals were closer to the center of core use areas; males participated more than females at distances further from the center of core use areas. Females participated in 44% of IGEs, with lactating females less likely to participate than cycling or pregnant females. Our findings suggest that high population density and overlapping ranges drive frequent and aggressive IGEs at Taboga and that escalation is shaped primarily by social rather than ecological factors. These results highlight the importance of social processes in territorial defense and underscore their role in shaping intergroup conflict in areas of high population density.

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

The Impact of Wind on Flow and Sediment Transport over Intertidal Flats - Irene Colosimo; Paul L. M. de Vet; Dirk S. van Maren; Ad J. H. M. Reniers; Johan C. Winterwerp; Bram C. van Prooijen (Journal of Marine Science and Engineering, 2020)
Sediment transport over intertidal flats is driven by a combination of waves, tides, and wind-driven flow. In this study we aimed at identifying and quantifying the interactions between these processes. A five week long dataset consisting of flow velocities, waves, water depths, suspended sediment concentrations, and bed level changes was collected at two locations across a tidal flat in the Wadden Sea (The Netherlands). A momentum balance was evaluated, based on field data, for windy and non-windy conditions. The results show that wind speed and direction have large impacts on the net flow, and that even moderate wind can reverse the tidal flow. A simple analytical tide–wind interaction model shows that the wind-induced reversal can be predicted as a function of tidal flow amplitude and wind forcing. Asymmetries in sediment transport are not only related to the tide–wind interaction, but also to the intratidal asymmetries in sediment concentration. These asymmetries are influenced by wind-induced circulation interacting with the large scale topography. An analysis of the shear stresses induced by waves and currents revealed the relative contributions of local processes (resuspension) and large-scale processes (advection) at different tidal flat elevations.

Molecular variation and population structure in critically endangered Turks and Caicos Rock Iguanas: identifying intraspecific conservation units and revising subspecific taxonomy - Mark E. Welch; Giuliano Colosimo; Stesha A. Pasachnik; Catherine L. Malone; Jace Hilton; June Long; Angela H. Getz; Allison C. Alberts; Glenn P. Gerber (Conservation Genetics, 2017)

A case of untreatable sciatica - Fabio Pilato; S. Gaudino; P. Profice; C. Colosimo; V. Di Lazzaro (Acta Neurologica Belgica, 2013)